Quasiparton distributions of pions at large longitudinal momentum - Zhang, Dao-yu; Huang, Chuang; Fu, Wei-jie (Physical review, 2025)
In this paper, we develop an approach to calculate the valence-quark quasiparton distribution amplitude (quasi-PDA) and quasiparton distribution function (quasi-PDF) for the pion with a large longitudinal momentum with the functional renormalization group (fRG). This is demonstrated in a low energy effective theory (LEFT) with four-quark scatterings. In the study of the complex structure of quasi-PDA, we introduce a deformed integration contour in the calculations of quasi-PDA or quasi-PDF, which allows us to obtain correct integrals for all momentum fractions. It is found that the pion light-front PDA extrapolated from quasi-PDA based on the large momentum effective theory in the LEFT is comparable with lattice QCD and Dyson-Schwinger equation. This work paves the way to study the PDA and PDF within the fRG approach to first-principles QCD.
Gesehen am 30.01.2026